Compliance, Informality and Contributive Pensions - Marie-Louise Leroux; Dario Maldonado; Pierre Pestieau (Center for Economic Studies and ifo Institute (CESifo), 2015)
We consider a political economy model in which agents have the possibility to hide part of their earnings in order to avoid taxation. Taxation is exclusively used to finance a pension system. If the pension system is implemented, agents in their old age receive a benefit which includes both a Bismarkian and a Beveridgian component. We show that in the absence of compliance costs, agents are indifferent to the tax rate level as in response, they can perfectly adapt their level of compliance. The public pension system is found to be at least partially contributory in order to increase compliance and thus to increase the tax base. When compliance costs are introduced, perfect substitutability between compliance and taxation breaks down. Depending on the relative returns from public pensions and private savings as well as on the elasticity of compliance to income, we obtain that the preferred tax rate should be increasing or decreasing in income. The majority voting tax rate is more likely to be positive when the median income is low and when the return from public pensions dominates that of private savings. The level of the Bismarkian pillar will now be chosen so as to account for increased political support, for increased direct redistribution toward the worst-off agent, and increased tax base.
Keywords: H55; D91; 330; compliance costs; majority voting; public pensions; tax evasion